Archaeological sites and palaeoenvironments of Pleistocene West Africa. Issue 4 (1st January 2022) - Cerasoni, Jacopo Niccolò; Hallett, Emily Y.; Ben Arous, Eslem; Beyer, Robert M.; Krapp, Mario; Manica, Andrea; Scerri, Eleanor M. L.
ABSTRACT: African paleoanthropological studies typically focus on regions of the continent such as Eastern, Southern and Northern Africa, which hold the highest density of Pleistocene archaeological sites. Nevertheless, lesser known areas such as West Africa also feature a high number of sites. Here, we present a high-resolution map synthesising all well contextualised Pleistocene archaeological sites present in Sub-Saharan West Africa. A detailed elevation and ecoregional map was developed and correlated with palaeoanthropological sites. This map is supplemented with 1, 000- and 2000-year interval climate reconstructions over the last 120, 000 years for three subregions of high archaeological interest. The presented archaeological sites were compiled by reviewing published literature, and selected based on: (1) documented archaeological stratification or >10 characteristic artefacts, (2) published coordinates, and (3) published chronometric ages or relative dating. The data presented here elucidates the current state of knowledge of Pleistocene West Africa, highlighting the regional potential for human evolutionary studies.